EFEK HEPATOPROTEKTIF EKSTRAK METANOL JAHE MERAH (Zingiber officinale Roscoe) PADA MENCIT JANTAN YANG DIINDUKSI CCl4 - Moch Saiful Bachri (Pharmaciana, 2011)
MeOH extract of Zingiber officinale Roscoe (ZO) were investigated for hepatoprotective effect at the doses (p.o) of 100 and 200 mg/kg body weight using CCl4 induction method. Male Swiss mouse (25±1,5 g) were treated with ZO doses 100 and 200 mg/kg bw and Sillymarin (100 mg/kg bw) for two week before treatment with a single dose of CCl4, 0.5 ml/kg bw, intraperitoneally. The mouse were sacrifactivity of SGPT-SGOT. The study showed the activity of SGPT of MeOH extract of ZO doses 100 mg/kg bw and 200 mg/kg bw, Sillymarin, control and normal groups are (34.51±5.34), (27.38±4.28), (27.26±1.06), (36.61±1.87), and (25.37±2.01) U/L, respectively. While the activity of SGOT of MeOH extract of ZO doses 100 mg/kg bw and 200 mg/kg bw, Sillymarin, control and normal groups are (88.88±0.94), (83.88±3.91), (83.99±7.24), (92.97±8.16), and (82.99±3.97) U/L, respectively. MeOH extract of ZO dose 200 mg/kg BW and Sillymarin significantly (p < 0,05) decrease the activities two enzymes (SGPT and SGOT). The results showed MeOH extract Zingiber officinale Roxb has hepatoprotective effect